The Epidemiology, Virology and Clinical Findings of Dengue Virus Infections in a Cohort of Indonesian Adults in Western Java - Kosasih, Herman; Alisjahbana, Bachti; Nurhayati; de Mast, Quirijn; Rudiman, Irani F.; Widjaja, Susana; Antonjaya, Ungke; Novriani, Harli; Susanto, Nugroho H.; Jusuf, Hadi; van der Ven, Andre; Beckett, Charmagne G.; et al. (PLOS Neglected Tropical Diseases, 2016)
Author Summary Dengue is the fastest spreading mosquito borne diseases in the world and is endemic in most tropical and sub-tropical countries with an estimated 96 million infections resulting in clinical disease annually. Population-based longitudinal prospective studies are essential for understanding dengue virus in the natural setting and developing prevention strategies to curtail the impact of disease. We present the results of a longitudinal cohort study of adults in West Java, Indonesia that was conducted between 2000–2004 and 2006–2009. We found that in adults, dengue virus was a significant cause of febrile illness. The entire spectrum of clinical severity was observed with most dengue virus infections manifesting as asymptomatic. The incidence of symptomatic dengue virus infections observed in this cohort was much higher than reported national or provincial rates. In addition, we observed all four dengue virus serotypes circulating during most years of the study.